Kualitas Layanan Dan Kepuasan Konsumen Warung Internet: Kota Malang - Ninik Lukiana; Hesti Budiwati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
Business services internet cafes are also very rampant in the city of Malang, a town in East Java Province. Consumers from Internet cafes are students, students and the general public. On the basis of this, the study tries to examine further the analysis of service quality and consumer satisfaction with Internet cafes in Malang using 5 dimensions of service quality. The highest rating in a row contained in the dimension of assurance, reliability, empathy, responsiveness, and tangible. When viewed under score gap that occurs, consumers are Internet cafes in Malang not satisfied with the quality of that which they receive service. Based on the analysis concluded that consumer expectations of service quality in tangible dimensions, reliability, responsiveness, assurance and empathy into the criteria is expected. Consumer assessment of current conditions of service in Malang Internet cafes in the fifth dimension into the criteria of service quality Fine. However, there is a negative score gap between consumer ratings and their expectations are defined as consumer dissatisfaction towards the quality of service internet cafes they have received.